The structure and development of self-consciousness : interdisciplinary perspectives - Zahavi, Dan; Grünbaum, Thor; Parnas, Josef (Advances in consciousness research ;, 2004)
Self-consciousness is a topic of considerable importance to a variety of empirical and theoretical disciplines such as developmental and social psychology, cognitive neuroscience, psychiatry, and philosophy. This volume presents essays on self-consciousness by prominent psychologists, cognitive neurologists, and philosophers. Some of the topics included are the infants' sense of self and others, theory of mind, phenomenology of embodiment, neural mechanisms of action attribution, and hermeneutics of the self. A number of these essays argue in turn that empirical findings in developmental psych.